Perbedaan Kontrol Diri Mahasiswa Dakwah Dan Komunikasi UIN Ar-Raniry Banda Aceh - Rofiqa Duri, Rofiqa (Prodi Bimbingan dan Konseling Islam, 2024)
This research was based on students from the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh who were unable to control themselves in the learning process. Students from the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh who are able to control themselves can be seen from the aspects of behavioral control, cognitive control and the ability to control decisions. Factors influencing self-control of students at the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh in terms of male and female gender. The self-control possessed by students from the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh will be able to direct and regulate their behavior in studying, so that they are not easily tempted and fall into negative changes and deviant behavior. This research aims to describe the self-control of students at the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh in terms of male and female gender. The research method used is quantitative descriptive. The population in this study were students from the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh. The sampling technique uses proportional random sampling. The instrument used is a Likert scale model. Data analysis using variance analysis techniques (ANOVA). The results of the research show that the self-control of students at the Faculty of Da'wah and Communication, UIN Ar-Raniry Banda Aceh is in the high category (T) and the self-control of students at the Faculty of Da'wah and Communication at UIN Ar-Raniry Banda Aceh in terms of gender, namely men are in the category medium (S) and women are in the high category (T).